(untitled) (Bangladesh Journal of Infectious Diseases, 2025)
All skin illnesses are categorized as Kushta Roga in Ayurveda. They are divided into two categories: Maha Kushta (major skin illnesses) and Kshudra Kushta (minor skin disorders). Eczema, or Atopic Dermatitis, is typified by xerosis and pruritus, featuring ill-defined patches of erythema and scaling. In its acute phase, eczema may manifest as vesicular and exudative, while the chronic phase is marked by hyperpigmentation and lichenification. Excoriations commonly occur, akin to the development of stretch marks. The clinical presentation of atopic dermatitis bears similarities to other forms of eczema, such as contact eczema, on an individual lesion level. Acute eczema is characterized by a vivid red infiltration with edema, vesicles, exudation, and crusting, whereas the subacute and chronic phases are dominated by lichenification, excoriations, papules, and nodules. The diagnostic approach incorporates factors like distribution and patient-specific characteristics. Acute eczema is precipitated by exposure to irritants or allergens, with the involvement of inflammatory mediators like prostaglandins and helper T cells. Clinical manifestations include redness, scaling, edema, exudation, crusting, and pruritus. Despite advancements in dermatology, specific treatments for eczema remain elusive in modern science, with antihistamines and topical steroids standing as the sole efficacious interventions. In the realm of Ayurveda, Shodhan and Shaman Aushadhis constitute the cornerstone of treatment for Vicharchika, aligning with a holistic approach to address both the root cause and symptoms of the condition. Bangladesh Journal of Infectious Diseases, December 2024;11(2):223-227